Development of a Short and ICD-11 Compatible Measure for DSM-5 Maladaptive Personality Traits Using Ant Colony Optimization Algorithms. - Kerber, André; Schultze, Martin; Müller, Steffen; Rühling, Rosa Maria; Wright, Aidan G. C.; Spitzer, Carsten; Krueger, Robert F.; Knaevelsrud, Christine; Zimmermann, Johannes (Assessment, 2022)
While Diagnostic and Statistical Manual of Mental Disorders–Fifth edition (DSM-5) Section III and ICD-11 (International Classification of Diseases 11th–Revision) both allow for dimensional assessment of personality pathology, the models differ in the definition of maladaptive traits. In this study, we pursued the goal of developing a short and reliable assessment for maladaptive traits, which is compatible with both models, using the item pool of the Personality Inventory for DSM-5 (PID-5). To this aim, we applied ant colony optimization algorithms in English- and German-speaking samples comprising a total N of 2,927. This procedure yielded a 34-item measure with a hierarchical latent structure including six maladaptive trait domains and 17 trait facets, the "Personality Inventory for DSM-5, Brief Form Plus" (PID5BF+). While latent structure, reliability, and criterion validity were ascertained in the original and in two separate validation samples (n = 849, n = 493) and the measure was able to discriminate personality disorders from other diagnoses in a clinical subsample, results suggest further modifications for capturing ICD-11 Anankastia.